Espécies de Meloidogyne Goeldi em cafeeiro no município de Araguari-MG - Carneiro, Franciele Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Araguari County represents one of the main national coffee production in Brazil. However, productivity is significantly affected by the parasitic root-knot nematodes which are cited as major pests for coffee plants. Therefore, this study was conducted in coffee plantations properties infested by nematodes in Araguari county, aiming to identify the present species. Soil and root samples from 18 coffee areas which presented depletion symptoms were collected and transported to the Laboratory of Nematologya, Departament of Plant Protection, UNESP/FCAV, Jaboticabal, SP for the study. The species were identified based on the morphology of the perineal pattern, morphology and morphometric of the lip males region, and also confirmed by esterase enzyme phenotype. In the studied populations, the identified species were: M. incognita which predominated in the plantations examined, followed by M. exigua, which was found in 5 properties sampled and M. paranaensis, found in only 3 samples. Also, in intermediate plants used as supplementary income like pumpkin (Cucurbita pepo L.), was found M. paranaensis and M. incognita. Moreover, a weed plant known as Momordica charantia L. was infected by a non-identified Meloidogyne specie. The information obtained in this study will be useful for developing these pest management programs

O município de Araguari representa uma das principais microrregiões produtoras de café no Brasil. Entretanto, a produtividade dos cafezais vem sendo sensivelmente reduzida em consequência dos danos causados pelos nematoides de galha (Meloidogyne spp.). Em face disso, este estudo foi conduzido em cafezais infestados por esses nematoides no mencionado município, com o objetivo de se identificar as espécies presentes. Foram coletadas amostras de solo e raízes em 18 cafezais no município, com sintomas de depauperamento e transportadas para o Laboratório de Nematologia do Departamento de Fitossanidade da UNESP/FCAV, Câmpus de Jaboticabal, SP para o estudo. As espécies foram identificadas com base na morfologia do padrão perineal e na morfologia e morfometria da região labial dos machos, e confirmadas pelo fenótipo isoenzimático para esterase. Nas populações estudadas, foram identificadas as espécies: Meloidogyne incognita, que predominou nos cafezais examinados; seguida de M. exigua, encontrada em 5 propriedades amostradas e M. paranaensis, presente em apenas 3 amostras. Também, foi registrado o cultivo de plantas intercalares utilizadas para complementação da renda dos produtores, como a abóbora, cujas raízes estavam infectadas por M. paranaensis e M. incognita. Na planta daninha melão-de-são-caetano (Momordica indica L.), coletada em um dos cafezais amostrados encontrou-se uma espécie de Meloidogyne não identificada. As informações obtidas neste estudo serão úteis para o desenvolvimento de programas de manejo dessas pragas
Keywords: Café; Café - Doenças e pragas; Nematoda em plantas; Identificação; Especies; Distribuição geografica; Meloidogyne; Agricultural pests